Strengthening Students’ Emotional Intelligence at Al-Ikhlas Vocational High School, Balikpapan - Kamma, Cahyasry Arya Sahangga; Yusuf , Iskandar (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This study aims to analyze the enhancement of students' emotional intelligence at Al Ikhlas Vocational High School (SMK). The research method used is observation and interviews. The results of the study show that students at SMK Al Ikhlas have different levels of emotional intelligence. The learning process indicates that students tend to interact with their peers for about 30 minutes since the start of the lesson, indicating emotional fatigue among students. The analysis also shows that students lack empathy towards teachers during the learning process. Therefore, it is important for the school and educational staff to understand these differences and use appropriate approaches to support the development of students' emotional intelligence. Enhancing students' emotional intelligence needs to be done through appropriate and individualized reinforcement. An emotion-based curriculum can also help students develop a better understanding of their own emotions and others. In conclusion, this research emphasizes the importance of enhancing students' emotional intelligence in creating a learning environment that supports the holistic development of students at SMK Al Ikhlas